Validation of the Dutch version of the critical‐care pain observation tool. Issue 3 (22nd December 2015) - Stilma, Willemke; Rijkenberg, Saskia; Feijen, Hilde M; Maaskant, Jolanda M; Endeman, Henrik
ABSTRACT: Background: Systematic assessment of pain is necessary for adequate treatment of pain. Patient self‐reported pain is a superior assessment but is of limited use for intubated patients in the intensive care unit. For these patients, the critical‐care pain observation tool (CPOT) has been developed. Aim: To perform a validation of the Dutch CPOT. Study design: Cross‐sectional observational study. Methods: The Dutch translation of the CPOT was used. Clinimetric characteristics were analysed in a cross‐sectional design. Internal consistency (Cronbach's alpha) was tested by collecting CPOT scores in patients at rest and during turning. Inter‐rater reliability was tested by collecting CPOT scores simultaneously by two different nurses who were blinded to each other's scores. Criterion validity (area under the curve, sensitivity and specificity) of the Dutch CPOT (index test) was analysed using patient self‐reported pain (reference test). Results: Cronbach's alpha was 0.56. During rest, the inter‐rater reliability was 0.38 (95% confidence interval (CI): 0.20–0.53). During turning, the inter‐rater reliability was 0.56 (95% CI: 0.42–0.68; area under the curve = 0.65 [95% CI 0.57–0.73]). At a threshold CPOT score of 2, the sensitivity and specificity were 39% and 85%, respectively. Conclusion: The Dutch CPOT is available for pain assessment in intubated patients unable to self‐report. Inter‐rater reliability is moderate. At the threshold, a CPOT score of 2, the sensitivity was 39% and the specificity of 85%. Relevance to clinical practice: The CPOT is easy to use for systematic assessment of pain. Additional information about the threshold is valuable for use in daily practice.